Correction: S1PR1 drives a feedforward signalling loop to regulate BATF3 and the transcriptional programme of Hodgkin lymphoma cells - Vrzalikova, K; Ibrahim, M; Vockerodt, M; Perry, T; Margielewska, S; Lupino, L; Nagy, E; Soilleux, E; Liebelt, D; Hollows, R; Last, A; Reynolds, G; et al. (Leukemia, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.